Effect of Temperature Gradient Direction in the Catalyst Nanoparticle on CNTs Growth Mode - Liu Shang-Bin; Kuo Cheng-Tzu; Lo An-Ya (Nanoscale Research Letters, 2010)
Abstract To improve the understanding on CNT growth modes, the various processes, including thermal CVD, MP-CVD and ECR-CVD, have been used to deposit CNTs on nanoporous SBA-15 and Si wafer substrates with C2H2 and H2 as reaction gases. The experiments to vary process parameter of ΔT, defined as the vector quantities of temperature at catalyst top minus it at catalyst bottom, were carried out to demonstrate its effect on the CNT growth mode. The TEM and TGA analyses were used to characterize their growth modes and carbon yields of the processes. The results show that ΔT can be used to monitor the temperature gradient direction across the catalyst nanoparticle during the growth stage of CNTs. The results also indicate that the tip-growth CNTs, base-growth CNTs and onion-like carbon are generally fabricated under conditions of ΔT > 0, <0 and ~0, respectively. Our proposed growth mechanisms can be successfully adopted to explain why the base- and tip-growth CNTs are common in thermal CVD and plasma-enhanced CVD processes, respectively. Furthermore, our experiments have also successfully demonstrated the possibility to vary ΔT to obtain the desired growth mode of CNTs by thermal or plasma-enhanced CVD systems for different applications.